2013
DOI: 10.1007/s10126-013-9495-2
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Detachment of Living Microorganisms Using a Potential-Controlled Electrode

Abstract: We developed an electrical modulation method for attachment and detachment of microorganisms. Living microorganisms suspended in non-nutritive media such as PBS(−) and artificial seawater were attracted by and selectively attached to indium tin oxide (ITO)/glass electrode regions to which a negative potential was applied. The microorganisms suspended in LB medium and glucose solution were not attracted to the ITO electrode. Dead microorganisms were not attracted to the ITO electrode. The living microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…The electrode-absorbed micro-organisms were released into artificial seawater (Nihon Pharmaceutical) by applying a triangular wave potential of ±10 mV, 9 MHz (Koyama et al, 2013). A portion of the retrieved suspension was then incubated in artificial seawater containing 0.5 % (w/v) ISP2 (MB; Difco) at 25 u C for 1 week for restoration of bacteria following electrical injury.…”
mentioning
confidence: 99%
“…The electrode-absorbed micro-organisms were released into artificial seawater (Nihon Pharmaceutical) by applying a triangular wave potential of ±10 mV, 9 MHz (Koyama et al, 2013). A portion of the retrieved suspension was then incubated in artificial seawater containing 0.5 % (w/v) ISP2 (MB; Difco) at 25 u C for 1 week for restoration of bacteria following electrical injury.…”
mentioning
confidence: 99%
“…Those isolation methods include a variety of physicochemical pretreatments such as phenol, calcium carbonate, salinity, antimicrobial treatment, heat, ultrasonic treatment, microwave and radio wave irradiation, and ionizing radiation. 3,24,30 In our previous study, we found that numerous actinomycetes including the genus Streptomyces could be electrically retrieved from deep-sea sediments 31 and cryopreserved marine sponges. 32 Living microorganisms suspended in nonnutritive solution such as PBS(¹) and artificial seawater (ASW) were selectively attached to a negative potential-applied optically transparent electrode against gravitational force.…”
Section: Introductionmentioning
confidence: 99%
“…31, 32 Microorganisms suspended in Luria-Bertani medium and glucose solution were not attracted to the electrode. 31 Dead microorganisms were also not attracted to the electrode. 31 We collected the electrically attached living microorganisms and then detached them from the electrode by applying a high-frequency wave potential in nonnutritive solution such as PBS(¹) or ASW.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations